Pengaruh Pengembangan Karir Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Syaiful Bahri; Yuni Chairatun Nisa (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
Career development is a process and activities to prepare an employee to occupy a position in an organization or company, which will be done in the future. The objective of this study was to determine whether there is influence career development and motivation on employee job satisfaction BPJS Employment Branch Office Belawan. Data collection techniques in this research is the study of documentation, interviews and questionnaires (questionnaire). Data analysis technique used is multiple regression analysis, the classical assumption test, hypothesis test (t test and F) and determination. The results of this study concluded that: (1) the career development have positive effect on job satisfaction which means that career development can improve employee job satisfaction; (2) motivation does not affect the job satisfaction; and (3) that the career development and motivation significantly influence job satisfaction.